Development of Economics Textbooks with a Contextual Approach Based on TPACK to Improve Problem-Solving and Creative Thinking Skills - Samakmur, Samakmur; Sari, Erlina; Vebrina, Dinda (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2025)
This study aims to develop an Economics Textbook using a Contextual Approach based on TPACK to improve students' problem-solving and creative thinking skills. The research employs a development research method using the ADDIE model, which consists of Analyze, Design, Development, Implementation, and Evaluation phases. The development process involved six expert validators who assessed the textbook's format, language, and content. Validation instruments were used to collect data and obtain feedback for improvement. The validity analysis was conducted using descriptive percentage analysis, calculating the Average Percentage Score (PRS) for each validated aspect. The results show that the Economics Textbook developed with a Contextual TPACK-based approach meets validity criteria. The average percentage scores (PRS) were 81 for format, 87.82 for language, and 83.13 for content, with an overall average of 83.98, all falling into the high category. This textbook is suitable for implementation in economics courses at the higher education level and is expected to significantly enhance students' critical thinking, collaboration, and problem-solving skills by promoting more active and meaningful learning experiences.